40th Art Festival Mito 2007. - Exhibition. 40th Art Festival Mito 2007. Contemporary Art Center Art Tower Mito Mito-shi. 2007-05-19. 2007-06-17 (Mito : Contemporary Art Center Art Tower Mito Mito-shi, 2007)
Isaka, Tadashi ; Isozaki, Toshimitsu ; Inoue, Juhaku ; Shimizu, Masaru ; Suzuki, Toshiyuki ; Ryouzou, Sutou ; Tanaka, Noriko ; Nojima, Seiji ; Hirato, Shirou ; Fukushima, Shiyo ; Machida, Hirobumi ; Matsuda, Masami ; Yamauchi, Koukaku ; Yoshizawa, Tesshi ; Omata, Hikaru ; Kakurai, Kazuo ; Kanbara, Seira ; Kido, Natsuo ; Gotou, Seiichi ; Komori, Kunio ; Sakaizumi, Atsushi ; Seki, Nantyu ; Yoshizawa, Tesseki
Japans
boek